AtFUT4 and AtFUT6 Are Arabinofuranose-Specific Fucosyltransferases - Soto, Maria J.; Prabhakar, Pradeep Kumar; Wang, Hsin-Tzu; Backe, Jason; Chapla, Digantkumar; Bartetzko, Max; Black, Ian M.; Azadi, Parastoo; Peña, Maria J.; Pfrengle, Fabian; Moremen, Kelley W.; Urbanowicz, Breeanna R.; et al. (Frontiers in Plant Science, 2021)
The bulk of plant biomass is comprised of plant cell walls, which are complex polymeric networks composed of diverse polysaccharides, proteins, polyphenolics, and hydroxyproline-rich glycoproteins (HRGPs). Glycosyltransferases (GTs) work together to synthesize the saccharide components of the plant cell wall. The Arabidopsis thaliana (A. thaliana) fucosyltransferases (FUTs), AtFUT4 and AtFUT6, are members of the plant-specific glycosyltransferase family 37 (GT37). AtFUT4 and AtFUT6 transfer fucose (Fuc) onto arabinose (Ara) residues of arabinogalactan proteins (AGPs) and have been postulated to be non-redundant AGP-specific FUTs. AtFUT4 and AtFUT6 were recombinantly expressed in mammalian HEK293 cells and purified for biochemical analysis. We report an updated understanding on the specificities of AtFUT4 and AtFUT6 that are involved in the synthesis of wall localized AGPs. Our findings suggest that they are promiscuous enzymes that are able to utilize various arabinogalactan (AG)-like and non-AG-like oligosaccharide acceptors, and only require a free, terminal arabinofuranose. We also report with GUS promoter-reporter gene studies that AtFUT4 and AtFUT6 gene expression is sub-localized in different parts of developing A. thaliana roots.